To Choose or Not to Choose: Contracts, Reference Points, Reciprocity, and Signaling - Mathias Erlei; Christian Reinhold (Verein für Socialpolitik, 2010)
Hart and Moore (2008) argue that varying degrees of flexibility in contracts induce differing reference points and aspiration levels for parties' shares of a transactions total surplus. As a consequence, a trade-off between adaptational flexibility and the prevention of distributional conflicts emerges. In a recent paper Fehr et al. (2009b) analyze a buyer-seller-relationship with incomplete contracts and ex ante uncertainty about the sellers' cost level to test these effects. We rerun their experiment and introduce another treatment with exogenously determined contract types. Like FHZ we find reference point effects in both treatments. However, uncooperative shading behavior in our treatments differs substantially from the one described in FHZ. Furthermore, it makes a significant difference whether contract types are determined by buyers or determined exogenously. We explain this by introducing two further effects, a reciprocity effect and a signaling effect.
Keywords: C91; D01; D23; 330; contracts; reference points; experiment